Urban Millennial Men's Perceptions of Justice and Gender Equality - Yurisna Tanjung; Atika Ulayya; Khaidir Ali (International Journal of Science and Society, 2023)
Gender equality in Indonesia began to be programmed when the Presidential Instruction of the Republic of Indonesia Number 9 of 2000 was issued regarding gender mainstreaming, meaning that understanding of gender equality in society began to be developed in the 2000s. However, not all people understand the meaning of gender equality so that the implementation of gender equality in the family is still far from expectations. Gender studies pay more attention to aspects of a person's masculinity or femininity. The specific objectives of this research are; to find out how millennial men perceive gender justice and equality. The research method uses a qualitative research design with a case study approach. The research results show that millennial men do not understand the term Gender Mainstreaming. However, they understand the terms gender equality and justice, they even have the perception that this is considered normal when women work in the public area and men work in the domestic area.